A decision support system for the development of voyage and maintenance plans for ships. (5th February 2015) - Diakaki, Christina; Panagiotidou, Natalia; Pouliezos, Anastasios; Kontes, Georgios D.; Stavrakakis, George S.; Belibassakis, Kostas; Gerostathis, Theodoros P.; Livanos, George; Pagonis, Dimitrios-Nikolaos; Theotokatos, Gerasimos
The waterborne sector faces nowadays significant challenges due to several environmental, financial and other concerns. Such challenges may be addressed, among others, by optimising voyage plans, and diagnosing as early as possible engine failures that may lead to performance degradation. These two issues are addressed by the decision support system (DSS) presented herein, which focuses on the operation of merchant ships. For the development of voyage plans, a multicriteria decision problem is developed and handled with the PROMETHE method, while a multivariable control chart is used for the fault diagnosis problem. A MATLAB-based software implementation of the DSS has been developed adopting a modular architecture, while, in order to provide a generic software solution, the required input data are retrieved from dedicated web-services, following specific communication and data exchange protocols.